The Influence of Socioeconomic Factors on the Epidemiology of Maxillofacial Fractures in Southern Italy. Issue 8 (November 2018) - Sbordone, Carolina; Barca, Ida; Petrocelli, Marzia; Dell'Aversana Orabona, Giovanni; Vaira, Luigi Angelo; Colangeli, Walter; Cristofaro, Maria Giulia; Giudice, Mario; Giudice, Amerigo; Cassandro, Francesco Maria; Attanasi, Federica; Iaconetta, Giorgio; et al.
Abstract : Abstract: Maxillofacial fractures represent a serious public health problem. Their epidemiology is extremely variable and its analysis is crucial to establish effective treatment and prevention of these injuries. The aim of this multicentric retrospective study was to analyze causes, demographics, incidence, characteristics of 987 patients diagnosed with maxillofacial trauma between 2011 and 2015 at Complex Operative Unit of Maxillofacial Surgery of Federico II University of Naples and Magna Graecia University of Catanzaro, Italy; 657 male and 310 female patients were admitted in the study. The most frequently observed fracture involved the mandible (399 patients, 35.4%), followed by zygomatic complex (337 patients, 29.9%), orbital walls (160 patients, 14.2%), and nasal bones (129 patients, 11.4%). The most frequent cause of fracture was assaults (30.4%), followed by road traffic injuries (27.2%), falls (23.2%), sport accidents (15.4%), and others causes (2.6%). Significant variations of etiology have been detected between the 2 hospitals in relationship with different migration flow trends and cultural and socioeconomic features. Epidemiological analysis of maxillofacial fractures is crucial to identify the trauma burden and to help in developing a more efficient system to plan resource allocation and to deliver care and preventive measures establishing clinical and research priorities for effective treatment and prevention of these injuries.